LEXIN - lexikon för invandrare - Gellerstam, Martin (LexicoNordica, 1999)
Bilingual dictionaries for immigrants have been produced in Sweden since the late seventies in the framework of the LEXJN project (LEXikon för IN vandrare), funded by the Swedish govemment. The main features of this project are discussed together with problems connected with the use of Swedish as a common denominator of the bilingual dictionaries and the possibilities of "translating" the Swedish base into other Scandinavian languages.